La gestión directiva y el cumplimiento de la normativa legal en las instituciones del circuito educativo Alaquez - Joseguango bajo, diseño de un manual de procedimientos académicos. - Cárdenas Barriga, Manuel Patricio (2015)
The key objective of this research is to guide the management directive to comply with current legislation by designing a manual of procedures in academic educational institutions circuit Aláquez - Joseguango Bajo. It was considered essential to respond to a problem that has become common in educational institutions where there are serious shortcomings in the directive management for compliance with legal regulations. In the research process methods and deductive hypothetical in the formulation of the hypothesis, the analytical presentation of the results of fieldwork in the deductive conclusions were used; the statistic in presenting the results of research and scientific method in preparing the final report. The results the research process reveal the urgent need of an academic procedures manual that facilitate the settlement qualifications and use of educational resources in the institutions. Finally, as a conclusion it is essential to note that the actions of a true directive leadership are the driving force and essence of the transformation of educational practices, for it is essential to develop strategies that make teacher professional performance be effective.